CLINICAL AND FUNCTIONAL PROFILE ANALYSIS OF MECHANICALLY VENTILATED PATIENTS IN THE INTENSIVE CARE UNIT (Interdisciplinary Studies Journal, 2026)
Mechanical ventilation is frequently required in critically ill patients with respiratory failure; however, it is associated with the development of Intensive Care Unit–Acquired Weakness (ICU-AW) and significant functional impairments resulting from prolonged immobilization, which may persist for years after hospital discharge. This study aimed to compare functional capacity and muscle strength in patients undergoing mechanical ventilation at the time of ICU discharge, considering the duration of ventilatory support. This retrospective study was conducted through the analysis of electronic medical records of patients admitted to an Intensive Care Unit. Mobility was assessed using the Intensive Care Unit Mobility Scale (IMS), which classifies functional status from bed rest to independent ambulation, while global muscle strength was measured using the Medical Research Council (MRC) scale, based on the grading of specific upper and lower limb muscle groups. A total of 362 patients were analyzed and divided into three groups according to the duration of mechanical ventilation. Longer ventilation times were associated with lower IMS and MRC scores, as well as greater clinical severity. In conclusion, prolonged mechanical ventilation negatively impacts mobility and muscle strength, with mobility emerging as the most sensitive and earliest affected functional marker.Keywords: Early Mobilization; Post-Intensive Care Syndrome; Mechanical Ventilation.
Keywords: Hospitalization